Characterization of haplotype diversity defined by discontinuous insertions/deletions within the intron 2 of iInterleukin 2 in different domestic chicken populations - Dan-Ping, Zhang; Hui-Jin, Zhao; Yu-Zhu Luo; Han Jianlin (Science Alert, 2011)
Chicken interleukin 2 (chIL-2), a primary cytokine excreted mainly by activated T cells, can significantly enhance immunity. The chIL-2 has been proven to play an important role not only in the host’s response to coccidiosis and salmonella among parasite and bacterial diseases but also in the host’s enhanced immune responses to vaccines. To examine the genetic polymorphisms and their potential impact on the structure and function of the chIL-2, we first reviewed the history of identification of chIL-2 mRNA and genomic DNA sequences and analyzed the distribution of nucleotide variation in both coding and intronic sequences that were deposited in the GenBank database. Then a short DNA fragment of 374 bp to 386 bp within chIL-2 intron 2, in which a number of discontinuous insertions/deletions (in/dels) were involved in defining major sequence variations and structures, was targeted for re-sequencing in this study. A total of 15 novel haplotypes were identified in 66 indigenous and commercial chickens sampled from six countries. Three major haplogroups were characterized by two big in/dels of eight and 11 nucleotides, of which one group seemed to have experienced a recent and rapid expansion associated with domestication. Complete chIL-2 genomic DNA sequences comprised of these haplotypes are expected to match the major structural lineages and groups within the coding and intronic sequences and to contribute to a deeper understanding of the evolution and function of chIL-2 gene.